Myocardial extracellular volume fraction quantification in an animal model of the doxorubicin-induced myocardial fibrosis: a synthetic hematocrit method using 3T cardiac magnetic resonance - Zhou, Z.; Wang, R.; Wang, H.; Liu, Y.; Lu, D.; Sun, Zhonghua; Yang, G.; Xu, Lei (AME Publishing Company, 2020)
Background: Visualization of diffuse myocardial fibrosis is challenging and mainly relies on histology. Cardiac magnetic resonance (CMR), which uses extracellular contrast agents, is a rapidly developing technique for measuring the extracellular volume (ECV). The objective of this study was to evaluate the feasibility of the synthetic myocardial ECV fraction based on 3.0 T CMR compared with the conventional ECV fraction. Methods: This study was approved by the local animal care and ethics committee. Fifteen beagle models with diffuse myocardial fibrosis, including 12 experimental and three control subjects, were generated by injecting doxorubicin 30 mg/m2 intravenously every three weeks for 24 weeks. Short-axis (SAX) and 4-chamber long-axis (LAX) T1 maps were acquired for both groups. The association between hematocrit (Hct) and native T1blood was derived from 9 non-contrast CMR T1 maps of 3 control beagles using regression analysis. Synthetic ECV was then calculated using the synthetic Hct and compared with conventional ECV at baseline and the 16th and 24th week after doxorubicin administration. The collagen volume fraction (CVF) value was measured on digital biopsy samples. Bland-Altman plots were used to analyze the agreement between conventional and synthetic ECV. Correlation analyses were performed to explore the association among conventional ECV, synthetic ECV, CVF, and left ventricular ejection fraction (LVEF). Results: The regression model synthetic Hct = 816.46*R1blood − 0.01 (R2=0.617; P=0.012) was used to predict the Hct from native T1blood values. The conventional and synthetic ECV fractions of experimental animals at the 16th and 24th week after modeling were significantly higher than those measured at the baseline (31.4%±2.2% and 36.3%±2.1% vs. 22.9%±1.7%; 29.9%±2.4% and 36.1%±2.6% vs. 22.0%±2.4%; all with P<0.05). Bland-Altman plots showed a bias (1.0%) between conventional and synthetic ECV with 95% limits of agreement of −2.5% to 4.4% in the per-subject analysis (n=21) and a bias (1.0%) between conventional and synthetic ECV with 95% limits of agreement of −2.4% to 4.3% in the per-segment analysis (n=294). Conventional and synthetic ECV were well correlated with CVF (r=0.937 and 0.925, all with P<0.001, n=10). Conclusions: Our study showed promising results for using synthetic ECV compared with the conventional ECV for providing accurate quantification of myocardial ECV without the need for blood sampling.